2019
DOI: 10.1080/21645515.2019.1643675
|View full text |Cite
|
Sign up to set email alerts
|

Combining antimalarial drugs and vaccine for malaria elimination campaigns: a randomized safety and immunogenicity trial of RTS,S/AS01 administered with dihydroartemisinin, piperaquine, and primaquine in healthy Thai adult volunteers

Abstract: Introduction: RTS,S/AS01 is currently the most advanced malaria vaccine but provides incomplete, short-term protection. It was developed for use within the expanded program on immunizations (EPI) for African children. Another use could be adding mass RTS,S/AS01 vaccination to the integrated malaria elimination strategy in the Greater Mekong Subregion (GMS), where multidrug-resistant P.falciparum strains have emerged and spread. Prior to evaluating RTS,S/AS01 in large-scale trials we assessed whether the vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Vaccine-linked chemotherapy has been proposed as an improved treatment strategy for parasitic diseases to both reduce infection and reduce morbidity ( Bergquist et al., 2005 ; von Seidlein et al., 2020 ). We were the first to demonstrate in mouse models of acute infection that vaccine-linked chemotherapy using a low dose of benznidazole and a low dose of vaccine, consisting of a stable squalene emulsion containing recombinant Tc24-C4 protein and a TLR4 agonist adjuvant, either E6020 or glucopyranosyl lipid A (GLA), which leads to greater reductions in parasite burdens, cardiac inflammation, and cardiac fibrosis when compared to BNZ or vaccine only treatment ( Jones et al., 2018 ; Cruz-Chan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine-linked chemotherapy has been proposed as an improved treatment strategy for parasitic diseases to both reduce infection and reduce morbidity ( Bergquist et al., 2005 ; von Seidlein et al., 2020 ). We were the first to demonstrate in mouse models of acute infection that vaccine-linked chemotherapy using a low dose of benznidazole and a low dose of vaccine, consisting of a stable squalene emulsion containing recombinant Tc24-C4 protein and a TLR4 agonist adjuvant, either E6020 or glucopyranosyl lipid A (GLA), which leads to greater reductions in parasite burdens, cardiac inflammation, and cardiac fibrosis when compared to BNZ or vaccine only treatment ( Jones et al., 2018 ; Cruz-Chan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the vaccine showed more protective effect in children living in lower transmission settings than in higher transmission settings (RTS,S Clinical Trials Partnership, 2015). A recent study in healthy adult Thai volunteers demonstrated that the RTS,S/AS01 vaccine was safe and immunogenic in this population and not affected by the concomitant administration of DP and primaquine, which are antimalarials commonly used in MDA (von Seidlein et al, 2020). These data support the use of ACTs in combination with malaria vaccine RTS,S/AS01 in MDA to accelerate P. falciparum elimination in Asia.…”
Section: Triple Artemisinin-based Combination Therapymentioning
confidence: 95%
“…These proteins can spontaneously enter the cells to form VLPs that subsequently serve as a vaccine [96]. In phase 3 clinical trials, this vaccine has been shown to reduce (~50%) the incidence of severe malaria in children between the ages of 5 and 17 months, with good safety and efficacy [69]. The vaccine can also induce moderate levels of CD4+ T cells and antibodies against CSP, a secreted protein of the sporozoite stage of the parasite [97].…”
Section: Research Progress On Vlp-based Vaccines In Developmentmentioning
confidence: 99%